If it's not what You are looking for type in the equation solver your own equation and let us solve it.
((b-1)/4)+((2b-3)/4)=b-(1/2)
We move all terms to the left:
((b-1)/4)+((2b-3)/4)-(b-(1/2))=0
We add all the numbers together, and all the variables
((b-1)/4)+((2b-3)/4)-(b-(+1/2))=0
We calculate fractions
(5b-7)/()+(-(b-4)/()=0
We calculate terms in parentheses: +(-(b-4)/(), so:We get rid of parentheses
-(b-4)/(
We multiply all the terms by the denominator
-(b-4)
We get rid of parentheses
-b+4
We add all the numbers together, and all the variables
-1b+4
Back to the equation:
+(-1b+4)
(5b-7)/()-1b+4=0
We multiply all the terms by the denominator
(5b-7)-1b*()+4*()=0
We add all the numbers together, and all the variables
(5b-7)-1b*()=0
We get rid of parentheses
5b-1b*()-7=0
We move all terms containing b to the left, all other terms to the right
5b-1b*()=7
| 2x=(-1/9)x^2 | | ((b-1)/4)+((2b-3)/4)=b-1/2 | | (3x^2)(8x)=0 | | 72=2x-8 | | ((b-1)/4)+(2b-3)/4=b-1/2 | | 7*4^x=89 | | 2(x-3)+5(x-1)=4 | | 5^(3x-1)=24 | | 5^3x-1)=24 | | (10x+30)=(8x-3) | | (4x+16)/(2x+4)=0 | | 2^x=1.03 | | G^2-8g+7=0 | | 7(2-x+9=2 | | (2x+4)/(4x+16)=0 | | (3x+15)+(2x)=90 | | (3x-15)+(2x)=90 | | 42=15+2x | | -7(2t+2)=42 | | -3u+12u+6=7u=30 | | -10(s+3)=-89 | | 12m+50=949.38 | | 2(r+3)-4r=18 | | (7x-8)^2=0 | | y=1.75+36 | | 23/x+10=1/4 | | -3x+10=-5+2x | | 3(x+1)-1-x-1=6 | | 15t^2-15t-13=0 | | 6x-3(6)=-18 | | 40x+5*1.5x*52=65000 | | 26=(-18)-11r |